POTENSIAL SAYURAN HYDROPHONIK SEBAGAI LAHAN BISNIS DI PONDOK PESANTREN TAHFIZ TSAMROTUL FUAD: POTENTIAL HYDROPONIC VEGETABLES AS BUSINESS LAND AT TAHFIDZ TSAMROTUL FUAD BOARDING SCHOOL - Ilyas, Rifa; Kaniati, Mia (Jurnal Pengabdian Kepada Masyarakat Patikala, 2023)
From the past, the understanding that was still attached to most people was that at Islamic boarding schools, people only focused on studying religion, not teaching them about life's problems faced in the world, for example how to do business. This condition is not always true, the proof is at the Tsamrotul Fuad Islamic Boarding School, which has only been operating for the past two years. Apart from students studying religion and general education, the students are also provided with farming lessons by utilizing the land in the pesantren environment which is still a lot of vacant land, where the empty land is utilized by the pesantren by planting vegetables such as hydroponic vegetables including: pakcoy vegetables, vegetables kale, and spinach vegetables. This research was conducted at the Tsamrotul Fuad Islamic Boarding School which is located at Perum Graha Winaya, Cintaraja Village, Singaparna District, Tasikmalaya Regency. In this research analysis consists of an analysis of the structure of costs, profits and efficiency. The hydroponic vegetable planting is carried out by the Tsamrotul Fuad Islamic Boarding School so that students can have the potential to become successful entrepreneurs if they are equipped with religious values as well as entrepreneurship.